2019
DOI: 10.1016/j.ajpath.2019.07.004
|View full text |Cite
|
Sign up to set email alerts
|

KH-Type Splicing Regulatory Protein Controls Colorectal Cancer Cell Growth and Modulates the Tumor Microenvironment

Abstract: KH-type splicing regulatory protein (KHSRP) is a multifunctional nucleic acid binding protein implicated in key aspects of cancer cell biology: inflammation and cell-fate determination. However, the role KHSRP plays in colorectal cancer (CRC) tumorigenesis remains largely unknown. Using a combination of in silico analysis of large data sets, ex vivo analysis of protein expression in patients, and mechanistic studies using in vitro models of CRC, we investigated the oncogenic role of KHSRP. We demonstrated KHSR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 73 publications
0
4
0
2
Order By: Relevance
“…It is assumed that the increase in KSRP protein expression contributed to the increased detection of the KSRP with symmetric arginine methylation. There are also recent reports that KSRP promotes CRC tumorigenesis and survival, [ 16 ] and that KSRP down‐regulation significantly sensitizes CRC cells to 5‐fluorouracil treatment. [ 17 ] In addition, the expression of GTPase‐activating protein‐binding protein 2, thyroid hormone receptor interactor 6, and ribosomal RNA small subunit methyltransferase B proteins showing an increased fold change in SDMA‐containing peptides in CRC tissues (Table S4, Supporting Information) were also overexpressed in CRC tissues compared to paired noncancerous tissues (Figure S3, Supporting Information).…”
Section: Figurementioning
confidence: 99%
“…It is assumed that the increase in KSRP protein expression contributed to the increased detection of the KSRP with symmetric arginine methylation. There are also recent reports that KSRP promotes CRC tumorigenesis and survival, [ 16 ] and that KSRP down‐regulation significantly sensitizes CRC cells to 5‐fluorouracil treatment. [ 17 ] In addition, the expression of GTPase‐activating protein‐binding protein 2, thyroid hormone receptor interactor 6, and ribosomal RNA small subunit methyltransferase B proteins showing an increased fold change in SDMA‐containing peptides in CRC tissues (Table S4, Supporting Information) were also overexpressed in CRC tissues compared to paired noncancerous tissues (Figure S3, Supporting Information).…”
Section: Figurementioning
confidence: 99%
“…Therefore, cellular macromolecule metabolic processes are of great significance to cancer cells. Regulatory region nucleic acid binding modulates the tumor microenvironment in colorectal cancer tumorigenesis [ 32 ]. Transcription regulator activity can regulate the proliferation or apoptosis of cancer cells by affecting cell proliferation-related genes and directly regulating the cell cycle [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we identified five SFs related to the prognosis of PTC patients. KHSRP was reported to be oncogenic in non-small lung cancer, colorectal cancer and PTC (40)(41)(42). Overexpression of KHSRP activated IFN-aJAK-STAT1 signaling pathway and induced lung cancer cell invasion and metastasis (40).…”
Section: Discussionmentioning
confidence: 99%